2015
DOI: 10.1097/mlr.0000000000000251
|View full text |Cite
|
Sign up to set email alerts
|

Eliminating Health Care Disparities With Mandatory Clinical Decision Support

Abstract: Background All hospitalized patients should be assessed for VTE risk factors and prescribed appropriate prophylaxis. To improve best-practice VTE prophylaxis prescription for all hospitalized patients, we implemented a mandatory computerized clinical decision support (CCDS) tool. The tool requires completion of checklists to evaluate VTE risk factors and contraindications to pharmacologic prophylaxis, and then recommends the risk-appropriate VTE prophylaxis regimen. Objectives To examine the effect of a qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
68
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 102 publications
(75 citation statements)
references
References 48 publications
(46 reference statements)
0
68
0
1
Order By: Relevance
“…No doubt, clinician and patient behaviors are strongly influenced by factors at the level of the organization, the health care environment, and the macro environment. In one study, organizational policy, i.e., mandatory clinical decision support, eliminated racial disparities in VTE prophylaxis (89). In another study, the elimination of copayments for cardiovascular therapy substantially reduced racial and ethnic disparities in patient adherence and cardiovascular outcomes (30).…”
Section: Principle 7 There Is a Continuum Of The Relative Proximal Imentioning
confidence: 99%
“…No doubt, clinician and patient behaviors are strongly influenced by factors at the level of the organization, the health care environment, and the macro environment. In one study, organizational policy, i.e., mandatory clinical decision support, eliminated racial disparities in VTE prophylaxis (89). In another study, the elimination of copayments for cardiovascular therapy substantially reduced racial and ethnic disparities in patient adherence and cardiovascular outcomes (30).…”
Section: Principle 7 There Is a Continuum Of The Relative Proximal Imentioning
confidence: 99%
“…Our prior studies demonstrated that order sets significantly improve performance, from a baseline compliance of risk‐appropriate VTE prophylaxis of 66% to 84% . In the current study, compliance was relatively flat during the BASE period, which included these order sets.…”
Section: Discussionmentioning
confidence: 51%
“…Assim, postula-se a necessidade do uso de ferramentas nas práticas de saúde que promovam um cuidado de qualidade e igualitário para os usuários, contribuindo para a redução das disparidades em saúde (25) .…”
Section: Discussionunclassified